Rehabilitation Practices in Patients With Moderate and Severe Traumatic Brain Injury. Issue 5 (September 2019) - Kreitzer, Natalie; Rath, Kelly; Kurowski, Brad G.; Bakas, Tamilyn; Hart, Kim; Lindsell, Christopher J.; Adeoye, Opeolu
Abstract : Objective: To characterize the indications, timing, barriers, and perceived value of rehabilitation currently provided for individuals with moderate or severe traumatic brain injury (TBI) admitted to the intensive care unit (ICU) based on the perspectives of providers who work in the ICU setting. Participants: Members ( n = 66) of the Neurocritical Care Society and the American Congress of Rehabilitation Medicine. Design: An anonymous electronic survey of the timing of rehabilitation for patients with TBI in the ICU. Main Measures: Questions asked about type and timing of rehabilitation in the ICU, extent of family involvement, participation of physiatrists in patient care, and barriers to early rehabilitation. Results: Sixty-six respondents who reported caring for patients with TBI in the ICU completed the survey; 98% recommended rehabilitative care while patients were in the ICU. Common reasons to wait for the initiation of physical therapy and occupational therapy were normalization of intracranial pressure (86% and 89%) and hemodynamic stability (66% and 69%). Conclusions: The majority of providers caring for patients with TBI in the ICU support rehabilitation efforts, typically after a patient is extubated, intracranial pressure has normalized, and the patient is hemodynamically stable. Our findings describe current practice; future studies can be designed to determine optimal timing, intensity, and patient selection for early rehabilitation.